MOTIF UNI EROPA MENGHAPUS VALIDITAS EUROPEAN UNION-UNITED STATES PRIVACY SHIELD DALAM MENGATASI KEJAHATAN SIBER BERDASARKAN KONSEP EUROPEAN NORMATIVE POWER: STUDI KASUS SCHREMS II - Isma Mufidah (2022)
Schrems II is a legal case at CJEU that discusses the data protection rights of EU citizens. The right of data protection relates to the transfer of data from the data subject of an EU citizen to a third country, which in this case is the US. This data transfer is carried out by Facebook originating from the US, which is considered a country that does not provide data protection regulations equivalent to those in the European Union, namely GDPR. For this reason, finally the Privacy Shield, which is a decision that has been made by both parties to regulate data protection issues in the electronic commerce of transatlantic companies, was declared invalid. In this study, three concepts in it include the concept of the EU regional regime which is reduced to the concept of European Normative power which analyzes the principles of the founding of the EU, the actions taken by the EU based on its normative claims, and the impact resulting from actions on the EU's normative claims. the. In addition, this research also uses the concept of cyber security and the right to protect personal data. This study uses a qualitative methodology with an explanatory type of research. While the wetness of the data used is internal validity, which is to build a cause-and-effect relationship. One way is to do an analysis using pattern matching. This is evidence in the concept of European Normative power which is trying to be explained in this study. Where the results of this study are that the EU has the power to spread norms, values, principles that exist within the EU to be developed outside the EU. In this case, the normative principles shown by the GDPR, the actions shown by the results of Schrems II which refers to the GDPR, and the extraterritorial impact that the GDPR has on the data protection regulations of multinational companies and the regulations of other countries' governments. The results of the CJEU's decision in the Schrems II Case show that in projecting its data protection policy, the European Union has high standards, where if countries want to be involved in the EU market, then equalization of data protection regulations must be carried out to be able to protect EU data rights. GDPR itself is considered to have principles that uphold respect for human rights and legal aspects of them, as evidenced by the origin of the values and principles of the GDPR.